The 10th Annual International Seminar on Trends in Science and Science Education (AISTSSE) 2023 (Sciendo, 2023)
Proceedings of the 10th Annual International Seminar on Trends in Science and Science Education (AISTSSE) 2023. This is the 10th meeting since it was first held in 2014 and the third virtual meeting due to the COVID-19 pandemic. This year's seminar focuses on the significant contribution of research to the development of technology in supporting Society 5.0. The theme of this exciting forum is'Future Mathematics, Natural Sciences, and Education Trends to Achieve Sustainable Development Goals for Addressing the Society 5.0 Challenge', which covers six main topics, including: 1. Fundamental and applied research in mathematics, including basic mathematics, applied mathematics, and statistics. 2. Fundamental and applied research in physics, including theoretical physics and computation, geophysics, materials science, and technology. 3. Fundamental and applied research in biology, including fundamental biology, applied biology, and biotechnology. 4. Fundamental and applied research in chemistry, including instrumentation, basic chemistry, and applied chemistry. 5. Science education. 6. Computer science. For this year's conference, we have invited six plenary speakers with solid expertise from different countries and regions: 1. Prof. Dr. Syawal Gultom, M.Pd – Universitas Negeri Medan, Indonesia, Prof. 2. Teresa J. Kennedy, Ph.D. (STEM Education) – University of Texas at Tyler, USA., Prof. Dr. 3. Yatimah Alias (Chemistry) Universiti Malaya, Malaysia; Sirilak Chumkiew, Ph.D. (Biology) 4. Assoc. Prof. TS Dr. Ahmad Kadri Junoh, Suranaree University of Technology, Thailand 5. (Mathematics) – Universiti Malaysia Perlis, Prof. Dr. Usmeldi, M.Pd. (Physics Education) – Universitas Negeri Padang We have invited speakers with expertise in different fields to initiate the presentations in parallel sessions: 1. Prof. Dr. Suyono, M.Pd. (Chemical Education), Universitas Negeri Surabaya 2. Prof. Dr. Mangasi Alion Marpaung, M.Si. (Physics), Universitas Negeri Jakarta, Endah 3. Retnowati, Ph.D. (Mathematics Education), Universitas Negeri Yogyakarta, 4. Hendra Susanto, Ph.D. (Biology), Universitas Negeri Malang Conference date, placeOctober 10th, 2023, Medan-North Sumatera-IndonesiaConference OrganizerFaculty of Mathematics and Natural Science, Universitas Negeri Medan Peer Review Process Instructions for Authors ABSTRACTING & INDEXING Baidu ScholarBayerische StaatsbibliothekBDSBoDBowker Book DataCiandoCNKI Scholar (China National Knowledge Infrastructure)DimensionsEBSCOExLibrisGoogle BooksGoogle ScholarNavigaReadCubeSemantic Scholar TDOne (TDNet)WorldCat (OCLC)X-MOL